Empowering Mothers In Monitoring Compliance with Blood Supplement Tablet (BST) And Date Consumption For Anemia Prevention - Lisnawati, Lisnawati; Putri, Nita Aulia (Ann Publisher, 2025)
Background: Anemia is one of the indirect causes of maternal death. Anemia in pregnancy is a condition in which the hemoglobin level in the blood is less than 11 grams, reducing the body's ability to transport oxygen to tissues. The prevalence of anemia in pregnant women in Indonesia was 27% in 2024. The incidence of anemia at the Jagapura Community Health Center, Cirebon Regency, was 18.4% in 2024. Management of anemia involves iron supplementation, dietary changes, and regular monitoring of hemoglobin levels. Dates are foods rich in iron and are part of the local wisdom of the Japura people. Aim: This research aims to address anemia in women by empowering mothers to improve compliance with the consumption of iron tablets and dates. Methods: A case study method is used. The intervention involved the mother and her husband in monitoring compliance with consuming one iron tablet and seven dates per day for 14 days. Mothers' adherence to taking supplements and nutritious foods is supported by the family's active role in monitoring and motivation. Results, There was an increase in the mother’s hemoglobin level and in maternal adherence to taking iron tablets and dates, from 10.1 g/dL to 10.9 g/dL. Conclusions and Implications. Empowering mothers and families to monitor compliance with iron tablets and date consumption effectively increases hemoglobin levels and reduces maternal and infant complications.